Insulin resistance and intestinal microbial metabolites in childhood obesity - N.Yu. Zavhorodnia; I.A. Klenina; O.M. Tatarchuk; O.I. Hrabovska; O.P. Petishko (Gastroenterologìa, 2022)
The article deals with the study on the content of fecal short-chain fatty acids (SCFA) and their association with insulin resistance in obese children. It was found that intestinal microflora in obese children is characterized by changes in the qualitative composition and increased metabolic activity of the intestinal microflora. A moderate increase of HOMA-IR is accompanied by elevated concentration of anti-inflammatory cytokines, the content of which correlates with that of acetic, propionic acid and a decrease in the metabolic activity of intestinal microflora. The progression of insulin resistance is accompanied by a further increase in the concentration of anti-inflammatory cytokines, the level of HOMA-IR correlates with the level of propionic SCFA. Thus, modulation of SCFA content may be a promising way of therapeutic influence to correct insulin resistance and obesity in children.